Penguatan Pendidikan Karakter Siswa Melalui Sosialisasi Stop Bullying Di Sdn 5 Meurah Mulia Desa Keeh - Isra Maulina; Sufrizal; M. Anzaikhan; Muslina; Asra; Ria Rahayu (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
Bullying is a long-standing problem among young people. Most bullying incidents involve school-aged children. Bullying often occurs at SDN 5 Meurah Mulia, Keeh Village. So that KPM group 40 students make socialization to strengthen the educational character of elementary school students. This stop bullying socialization activity was held to reduce and anticipate problems that often occur in minors. The objectives of this socialization include the following: 1). To build relationships and spread awareness about the need to stop bullying against children at SDN 5 Meurah Mulia; 2). To outline policies to stop and deal with bullying against elementary school students; 3. To teach school children in Keeh Village about the importance of social roles. The community service methods applied in the activity are observation, discussion and lecture or presentation. The result of this stop bullying socialization activity is that the personality or character education of children begins to form in a better direction and finds mutual respect and appreciation among friends. Bullying can be avoided by starting early to foster understanding among students. This will help inform and educate the children of SDN 5 Meurah Mulia on how to prevent bullying.